2013
DOI: 10.1123/jpah.10.2.249
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pedometers for Monitoring Physical Activity in Children and Adolescents: Measurement Considerations

Abstract: Additional Information:• As accepted for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 79 publications
(109 reference statements)
4
86
0
26
Order By: Relevance
“…Despite heterogeneity across studies in the meta-analyses and the lack of association in some statistically tested comparisons, confidence in this finding has been strengthened by the relative consistency of evidence for both MVPA and TPA. Results are also consistent with studies that have assessed physical activity by pedometer and other objective methods [1719]. …”
Section: Discussionsupporting
confidence: 90%
“…Despite heterogeneity across studies in the meta-analyses and the lack of association in some statistically tested comparisons, confidence in this finding has been strengthened by the relative consistency of evidence for both MVPA and TPA. Results are also consistent with studies that have assessed physical activity by pedometer and other objective methods [1719]. …”
Section: Discussionsupporting
confidence: 90%
“…activity changes as a result of wearing the pedometer) could influence the validity of the study results. To improve the chances of valid results, a seven-day study design was used as no reactivity was reported in a meta-analysis by Clemes et al 15 No reactivity was observed in the statistical analysis.…”
Section: Limitations and Commentsmentioning
confidence: 99%
“…Additionally, they are a very effective tool for self-monitoring and motivation. Pedometers are easily interpretable and accessible as they provide an immediately visible display of accumulated step counts, a function not available in accelerometers (Clemes and Biddle 2013). However, only one study used the pedometer to assess the physical activity of children with ASD (Kodish et al 2006).…”
Section: Measurement Toolsmentioning
confidence: 99%